Thermal Diffusion in Binary Mixtures: Transient Behavior and Transport Coefficients from Equilibrium and Nonequilibrium Molecular Dynamics - Bonella, Sara; Ferrario, Mauro; Ciccotti, Giovanni (Langmuir, 2017)
Equilibrium and nonequilibrium molecular dynamics simulations are combined to compute the full set of coefficients that appear in the phenomenological equations describing thermal transport in a binary mixture subject to a constant thermal gradient. The Dynamical Non-Equilibrium Molecular Dynamics approach (D-NEMD) is employed to obtain the microscopic time evolution of the density and temperature fields, together with that of the mass and energy fluxes. D-NEMD enables one to study not only the steady state, but also the evolution of the fields during the transient that follows the onset of the thermal gradient, up to the establishment of the steady state. This makes it possible to ensure that the system has indeed reached a stationary condition, and to analyze the transient mechanisms and time scales of the mass and energy transport. A local time averaging procedure is applied to each trajectory contributing to the calculation to improve the signal-to-noise ratio in the estimation of the fluxes and to obtain a clear signal with the, relatively limited, statistics available.